The Birth of East-Belgian Identity and the Treaty of Versailles. A Critical Legal Analysis - Vanhullebusch, Matthias (Nationalities Papers, 2025)
„In the former districts of Eupen and Malmedy, present-day East-Belgians, in particular academic and socio-political elites, draw their collective identity, amongst others, from the historical injustices inflicted upon them ever since the adoption of the Treaty of Versailles. The transfer of sovereignty from Germany to Belgium was then the subject of a popular consultation organised by the transitional Belgian authorities in those territories. Favouring national over popular sovereignty, those authorities de facto undermined the freedom of choice and imposed their annexation to Belgium which the League of Nations, despite criticisms, consecutively endorsed. Much has been said about this petite farce belge yet not from a legal point of view. Thus, this article sheds a different light on the historical accounts of those events which are instrumentalised to construct the contemporary collective identity of the German-speaking Community of Belgium.“
Keywords: Identität; Nationalismus; Versailler Vertrag (1919)

„A trip organised for children is not a serious matter“? Summer treatment camps for the Belgian-German borderlands (1919–1939). - Venken, Machteld (Childhood, 2025)
„Although the children whose rural homelands transitioned from German to Belgian state sovereignty following the First World War were not the typical demographic targeted for preventive air treatments against tuberculosis, they were overrepresented in treatment camps in both Belgium and Germany. Nation-state representatives provided public and private (although partly state subsidized) treatment camps to restore the physical vitality, ethical integrity, and national allegiances of the minors. The parallel competitive offer took the form of a cross-border mixed economy of child welfare. Borderland residents either opportunistically supported the Belgian or German initiatives, or provided their own alternatives to protect their children from indoctrination.“
Keywords: Heilanstalt; Jugend; Kind; Nationalbewusstsein; Nationalismus; Nationenbildung; Verschickung

Vom Europäischen Krieg zum Weltkrieg. Militär und Kriegserfahrung während 130 Jahren - Liemann, Bernhard; Beck, Philippe; Quadflieg, Peter M.; Rohrkamp, René (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Grenzgebiet; Militär; Nationalismus

Auf dem Weg zu Nation und Nationalismus. Neue Staaten: nach innen geeinte Nationen, nach außen Großmächte - Liemann, Bernhard; Scharte, Sebastian (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Grenzgebiet; Nationalbewusstsein; Nationalismus; Nationenbildung

Die Verwaltung des Alltags als Ziel des Staates. Nationenbildung, Bürokratisierung, Demokratisierung und Sozialstaat - Scharte, Sebastian (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Demokratie; Grenzgebiet; Nationalbewusstsein; Nationalismus; Sozialstaat; Verwaltung

Nationalization campaigns and teachers’ practices in Belgian–German and Polish–German border regions (1945–1956) - Venken, Machteld (Nationalities Papers, 2014)
Keywords: Belgien; Bildungswesen; Deutschland; Eupen-Malmedy; Lehrer; Nationalismus; Polen; Schule; Sprachpolitik

Which Political Nation? Soft Borders and Popular Nationhood in the Rhineland, 1800–1850 - Brophy, James M. (Nationhood from Below. Europe in the Long Nineteenth Century, 2012)
Keywords: Nationalbewusstsein; Nationalismus; Nationenbildung; Rheinland

Vom Bestreben, "auch an den äußersten Westmarken nach Kräften der vaterländischen Sache zu dienen". Die rheinpreußischen Grenzkreise Eupen und Malmedy 1815–1914 - Scharte, Sebastian (Transregionale Perspektiven. Kleinräumige Mobilität und Grenzwahrnehmung im 19. Jahrhundert, 2011)
Keywords: Nationalbewusstsein; Nationalismus; Ostbelgien; Staatsgrenze

Germans, German Belgians, German-speaking Belgians - Jenniges, Hubert (Nationalism in Belgium. Shifting identities 1780–1995, 1998)
Keywords: Deutschsprachige Gemeinschaft; Grenzgebiet; Nationalbewusstsein; Nationalismus